Using Videos to Support Facilitators in Teacher Learning Circles - Kanyoza, Charity; Plaut, Daniel; Kumasewera, Pilirani (EdTech Hub, 2025)
This report presents findings from a design-based implementation research (DBIR) initiative conducted in partnership with Malawi’s National Numeracy Programme (NNP) to strengthen facilitation of Teacher Learning Circles (TLCs). TLCs are a core component of the NNP’s school-based continuous professional development model, yet as the programme scaled, many peer facilitators required additional, ongoing support to effectively guide sessions and model instructional practice. To address this gap, the research team co-designed short, practical videos aimed at reinforcing TLC structure and demonstrating key numeracy teaching activities. The study involved iterative video development, school-based user testing, and a comparative assessment of video dissemination modalities across 30 schools in two districts. Findings indicate that the videos enhanced facilitator preparedness, confidence, and modelling quality, with facilitators and teachers reporting clearer understanding of TLC objectives and related instructional strategies. WhatsApp emerged as the preferred distribution modality due to accessibility and familiarity, although data constraints and uneven device access highlight the need for flexible, multi-modal delivery approaches. The study concludes that targeted modelling videos, accompanied by clear usage guidance, can meaningfully strengthen facilitator-led professional development, particularly when dissemination strategies are adapted to local contexts. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence